(untitled) (Biological Sciences - PJSIR, 2022)
Salicylic acid (SA) is considered an important plant hormone that controls many aspects of plant growth and development, as well as resistance to biotic and abiotic stresses. In current investigations, a pot experiment consisting of four different levels of SA (0, 1, 2 and 3 mM SA) were tested on growth and physiological attributes of muskmelon (Cucumis melo L.), grown at different salinity levels (0, 50, 100 mM NaCl). Results revealed that all the morphological and physiological attributes were significantly (P<0.05) adversely affected by salinity stress, whereas application of SA improved growth rate of muskmelon both in saline and non-saline conditions. SA treated plants showed higher total chlorophyll content, photosynthetic rate and stomatal regulations as compared to control plants. SA application reduced the salt deleterious effects by inhibiting toxic Na+ ions accumulation in leaf and increased K+/Na+ ratio. Among the various applied concentrations, 2 mM SA increased shoot fresh weight by (30%), dry weight (34%), leaf area (25%) and K+/Na+ ratio by (84%) as compared to control plants. Thus, 2 mM SA concentration is concluded to be the best ameliorative treatment in salt stressed environments to enhance the muskmelon production.